Retrospective three-dimensional analysis of bone resorption volumes of free microvascular scapular and fibular grafts - Taxis, Juergen; Nobis, Christopher-Philipp; Grau, Elisabeth; Kesting, Marco; Moest, Tobias (British journal of oral & maxillofacial surgery, 2022)
Defects in head and neck regions are standardly treated with microvascular grafts, such as free scapular (SFF) and fibular flaps (FFF), which are subject to a certain amount of bone resorption over time. The aim of this study was the 3-dimensional evaluation of bone resorption volume in both grafts. Over a period of 10 years, computed tomograms (CT) of patients with mandibular reconstructions with SFFs and FFFs were examined. The respective grafts were segmented as well as 3-dimensionally measured. Furthermore, factors such as gender, age, nicotine abuse, previous disease with type 2 diabetes, and adjuvant therapies, were examined for their influence. A total of 211 CT scans from 67 patients (40 SFFs and 27 FFFs) were included in the study. SFFs showed slightly higher median bone volumes (87.60% at 730 days and 86.55% at 1500 days) than FFFs (84.40% at 730 days and 82.10% at 1500 days). When final volumes were considered, FFFs had higher mean volume values (88.22%) than SFFs (83.82%), with significant correlation between resorption volume and time progression (r = 0.357, p = 0.024). All previously mentioned factors had no significant effect on bone resorption. Bone volumes of FFFs showed postoperative volume reductions similar to those of SFFs, with isolated SFFs having markedly lower volume values. The choice of a microvascular graft for reconstruction in the mandible proves difficult regarding bone resorption. The presented results may support decisions about future transplantations.